MODERASI PROFITABILITAS PADA PENGARUH AGRESIVITAS PAJAK DAN LEVERAGE TERHADAP CORPORATE SOCIAL RESPONSIBILITY - Ayunita Ajengtiyas Saputri Mashuri (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2020)
This study uses quantitative research that aims to see whether tax aggressiveness and leverage have an effect on the disclosure of Corporate Social Responsibility (CSR) with profitability as variable moderation. This study was use a manufacturing company within sub-sector of consumer goods industry listed on the “Indonesia Stock Exchange. Samples were selected by purposive sampling and collected 16 companies of consumer goods industry sub-sectors during 2014-2018 research datas period. Testing the hypothesis in this  study using “Multiple Linear Regression Analysis with” a significance level of 5% (0.05). The results of this study indicates that;(1) Tax aggressiveness “has a significant effect on” CSR disclosure, (2) “Leverage does not have a significant effect on CSR disclosure”, (“3) Profitability measured using Return on Assets (ROA”) is able to strengthen Tax Aggressiveness and unable to strengthen leverage to influence CSR disclosure. Tax aggressiveness and leverage and profitability variables as moderating variables can explain the CSR disclosure variable by 52.1%.